Emotions and performance in rugby - Campo, M.; Champely, S.; Lane, A. M.; Rosnet, E.; Ferrand, C.; Louvet, B. (Journal of Sport and Health Science, 2019)
Purpose: This study investigated emotion-performance relationships in rugby union. We identified which emotions rugby players experienced and the extent to which these emotions were associated with performance, considering how emotions unfold over the course of a game, and whether the game was played at home or away. Methods: Data were gathered from 22 professional male rugby union players using auto-confrontation interviews to help identify situations within games when players experienced intense emotions. We assessed the intensity of emotions experienced before each discrete performance and therefore could assess the emotion-performance relationship within a competition. Results: Players identified experiencing intense emotions at 189 time-points. Experts in rugby union rated the quality of each performance at these 189 time-points on a visual analog scale. A Linear Mixed Effects model to investigate emotion-performance relationships found additive effects of game location, game time, and emotions on individual performance. Conclusion: Results showed 7 different pre-performance emotions, with high anxiety and anger associating with poor performance. Future research should continue to investigate emotion-performance relationships during performance using video-assisted recall and use a measure of performance that has face validity for players and coaches alike.